THE USE OF EUROPEAN UNION FUNDS FOR CULTURAL PURPOSES IN MAŁOPOLSKIE VOIVODSHIP FROM 2007 TILL 2015 - Powęska, Halina (Acta Scientiarum Polonorum. Oeconomia, 2018)
The paper explores the issue of the use of European Union funds for cultural heritage in Małopolskie Voivodship during the period 2007–2015, taking into consideration spatial categories which include: rural areas comprising rural communes and small towns, towns with health resorts, land counties, urban counties (town with county rights), and Cracow as the capital of the Voivodship. It examines the structure of the total value and of the amount of EU funding for culture-related European projects by the purposes of their implementation which included: revaluation of the objects of culture, creation and development of a new tourism product, renovation of sports and recreation facilities, promotion and other issues. The study was conducted using the statistical database of the National Information System of the Ministry of Infrastructure and Development of the Republic of Poland (KSI SIMIK 07-13) as of 31 December 2015.